2002
DOI: 10.1080/00288233.2002.9513515
|View full text |Cite
|
Sign up to set email alerts
|

The potential for phosphorus loss in relation to nitrogen fertiliser application and cultivation

Abstract: The amounts and forms of dissolved phosphorus (P) leached from undisturbed and cultivated soil in lysimeters were measured from sites that had received N fertiliser at 0, 200 or 400 kg N ha -1 yr -1 for 4 years. Soil in mini-lysimeters, 18 cm i.d. by 25 cm depth, was leached at monthly intervals over autumn and winter (500 mm total drainage) to simulate a relatively wet autumnwinter for eastern Southland (typical drainage, c. 350 mm yr -1 ). The major form of P leached was dissolved organic P (DOP), which repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Excluding N fertilization may have had a greater influence on P leaching than the P fertilization regime had. Similar results, with increased P leaching when N fertilization was excluded, were reported by McDowell and Monaghan (2002). However, Williams and Young (1994) observed a decrease in P leaching when N fertilization was excluded.…”
Section: Measured Phosphorus Concentrations In Drainage Water and Phosupporting
confidence: 76%
“…Excluding N fertilization may have had a greater influence on P leaching than the P fertilization regime had. Similar results, with increased P leaching when N fertilization was excluded, were reported by McDowell and Monaghan (2002). However, Williams and Young (1994) observed a decrease in P leaching when N fertilization was excluded.…”
Section: Measured Phosphorus Concentrations In Drainage Water and Phosupporting
confidence: 76%
“…The same study observed that dominant preferential flow (macropores) could by-pass high sorption capacity in the subsoil and give high losses in other soils. No-till practices may enhance preferential flow (Persson 2001;Petersen et al 1997;McDowell and Monaghan 2002).…”
Section: Background: Leaching and Transport Of Phosphorusmentioning
confidence: 99%
“…Thus, for subsurface flow, a short-term (30 min) extraction of soil with 0.01M CaCl 2 at a soil to solution ratio of 1:5 was designed by Schofield (1955) to simulate the correct ionic strength for soil solution in near-neutral pH and calcareous soils. This test has been used recently for the prediction of P behaviour and concentration in subsurface flow in the United Kingdom, United States, and New Zealand (McDowell & Condron 1999;McDowell & Sharpley 2001;Blake et al 2002;McDowell & Monaghan 2002;McDowell unpubl.). The data for these studies is plotted in Fig.…”
Section: Laboratory Extractions For P Loss Estimationsmentioning
confidence: 99%
“…Since all of the soils were under grassland when sampled, it is not surprising to see the least variation is evident in pH, while other chemical parameters such as Olsen P, organic C, and % P retention reflect their pedological origin and probably recent fertiliser management ( Table 2). The soils selected to evaluate a quick laboratory test to predict P in overland flow represent a wide ranging subset of soils from this group, while data from the literature is used to show the validity of an established quick laboratory test for P in subsurface flow (McDowell & Sharpley 2001;McDowell & Monaghan 2002).…”
Section: Laboratory Extractions For P Loss Estimationsmentioning
confidence: 99%
See 1 more Smart Citation